2020
DOI: 10.3389/fpsyg.2020.558234
|View full text |Cite
|
Sign up to set email alerts
|

Re-Living Suspense: Emotional and Cognitive Responses During Repeated Exposure to Suspenseful Film

Abstract: Arguments about the effects of repeated exposure to a suspenseful narrative raise controversial disputes over the paradox of suspense. The lexical meaning and the theoretical analyses of suspense imply that suspense cannot be experienced repeatedly because, in such cases, the knowledge from prior viewings and the resolution of outcome will eliminate tension and suspense. However, previous studies have argued that suspense can be re-experienced even when the participants know the outcome or repeatedly confront … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…This outcome is in line with the result of Nabi's study (Nabi et al, 2016). The individuals with preferences for suspense movies more probably have lower stress due to the repeated exposure to suspenseful movies, which might have a lower skin conductance level (SCL) and ECG that result in affective habituation or desensitization to repeated stimuli (Chun et al, 2020). And extant research has found that suspenseful film clips led to decreases in cortisol (Hubert and de Jong-Meyer, 1991).…”
Section: Discussionsupporting
confidence: 71%
“…This outcome is in line with the result of Nabi's study (Nabi et al, 2016). The individuals with preferences for suspense movies more probably have lower stress due to the repeated exposure to suspenseful movies, which might have a lower skin conductance level (SCL) and ECG that result in affective habituation or desensitization to repeated stimuli (Chun et al, 2020). And extant research has found that suspenseful film clips led to decreases in cortisol (Hubert and de Jong-Meyer, 1991).…”
Section: Discussionsupporting
confidence: 71%
“…However, Hubert and deJong-Meyer (1991) found that film suspense was associated with increased skin conductance, but also heart rate deceleration, a pattern often associated with attention and cognitive effort (Fisher et al, 2018;Lang, 2000Lang, , 2006Potter et al, 2018). However, in the study by Chun et al (2020), there was no difference in heart rate during firstand second-time exposure despite the expectation of dwindling attention during re-viewing. The authors attribute this result to the fact that heart rate is a parameter with low specificity, as it is "…associated with multiple cognitive and emotional processes, such as attention, information encoding, emotional arousal, and positive/negative emotional responses" (p. 10).…”
mentioning
confidence: 89%
“…Likewise, prolonged, and discrete increases in SCL have been found to occur when (a) narratives create uncertainty and ambiguity (Sparks, 1989) and (b) when that uncertainty is suddenly resolved (Roberts and Hoetzl, 2007). Corroborating the role of uncertainty in physiological audience responses, Chun et al (2020) showed that SCL systematically decreased during repeated exposure to the same suspenseful film clips, indicating lower arousal when the ending was known. Zillmann et al (1975) found that heart rate (HR) commonly rises during exposure to suspenseful media stimuli and drops when narrative suspense is resolved.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Gradually, the male protagonist begins to be impatient and even violent towards his sister, indicating that the seeds of conflict have already been planted inside the male protagonist, and the first layer of suspense is revealed. The evil thoughts within the hero are a superimposed and deepening process [4]. At first, he might just want to leave his sister at the crossroads and let the heavens decide what his fate will be.…”
Section: Narrative Structure and Visual Presentationmentioning
confidence: 99%